Vicarious liability in the common law world - Giliker, Paula (London : Hart Publishing, 2022)
This book is the one place to find unprecedented access to case-law, doctrinal debates and comparative reflections on vicarious liability from across the common law world. The doctrine of vicarious liability, that is strict liability for the torts of others, represents one of the most controversial areas of tort law. Unsurprisingly it is a doctrine that has been discussed in the highest courts of common law jurisdictions. This collection responds to uncertainties as to the operation of vicarious liability in twenty-first century tort law by looking at key common law jurisdictions and asking expert scholars to set out and critically analyse the law, identifying factors influencing change and the extent to which case-law from other common law jurisdictions has been influential. The jurisdictions covered include Canada, England and Wales, Australia, Singapore, Ireland, Hong Kong and New Zealand. In providing critical analysis of this important topic, it will be essential and compelling reading for all scholars of tort law and practitioners working in this field.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Keywords: Common law; Respondeat superior -- English-speaking countries; Torts / Delicts